2017
DOI: 10.2337/db16-1410
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Postprandial Hyperglycemia in Zucker Diabetic Fatty Rats With an SGLT2 Inhibitor Restores Glucose Effectiveness in the Liver and Reduces Insulin Resistance in Skeletal Muscle

Abstract: Ten-week-old Zucker diabetic fatty (ZDF) rats at an early stage of diabetes embody metabolic characteristics of obese human patients with type 2 diabetes, such as severe insulin and glucose intolerance in muscle and the liver, excessive postprandial excursion of plasma glucose and insulin, and a loss of metabolic flexibility with decreased lipid oxidation. Metabolic flexibility and glucose flux were examined in ZDF rats during fasting and near-normal postprandial insulinemia and glycemia after correcting exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
2
37
1
Order By: Relevance
“…However, a previous rat model of early type 2 diabetes showed that SGLT2 inhibitor reduces RQ. In the present study, the participants were well past early diabetes and lacked metabolic control, which might have contributed to the higher fasting RQ that was different from the animal study. Furthermore, the postprandial RQ elevation (postprandial 30 and 90 min, compared with the fasting), which represents postprandial metabolic flexibility, was abolished in the insulin + dapagliflozin group relative to the elevation observed in the insulin group.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…However, a previous rat model of early type 2 diabetes showed that SGLT2 inhibitor reduces RQ. In the present study, the participants were well past early diabetes and lacked metabolic control, which might have contributed to the higher fasting RQ that was different from the animal study. Furthermore, the postprandial RQ elevation (postprandial 30 and 90 min, compared with the fasting), which represents postprandial metabolic flexibility, was abolished in the insulin + dapagliflozin group relative to the elevation observed in the insulin group.…”
contrasting
confidence: 53%
“…Hyperglycemia is known to impair energy substrate oxidation in fasting and postprandial states, through impaired utilization of the intracellular energy source. Insofar as increased elimination of glucose into the urine is expected to reduce glucose availability, which can be used as an intracellular energy source.…”
mentioning
confidence: 99%
“…SGLT2Is have been shown to increase skeletal muscle glucose uptake 520 and reduce insulin resistance at the skeletal muscle. 521 In an animal model of high fat, diet-induced obesity, canagliflozin was shown to induce expression of IGF-1, protect against muscle mass loss, and restore the contractile force of muscle, 522 suggestive of a protective role for SGLT2Is on skeletal muscle.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…In our case, spontaneous regression of HCC was observed after SGLT2i treatment; no other clinical report has shown an association between SGLT2i treatment and spontaneous regression of HCC. However, SGLT2i is known to reduce insulin resistance in skeletal muscle of Zucker diabetic fatty rats . As insulin resistance is a potent risk factor for HCC proliferation, SGLT2i might suppress HCC through an improvement of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%